2021
DOI: 10.1353/cpr.2021.0006
|View full text |Cite
|
Sign up to set email alerts
|

Engaging LGBTQ Communities in Community-Partnered Participatory Research: Lessons from the Resilience Against Depression Disparities Study

Abstract: WORK-IN-PROGRESS & LESSONS LEARNEDdepression, 2-4 while transgender adults have a nine times greater lifetime risk for suicide attempts. 5 LGBTQ individuals from racial or ethnic minority groups may face additional challenges, owing to the intersections of discrimination from race/ethnicity and sexual/gender minority status. 6,7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…A systematic review examining culturally competent care for the LGBTQ + community seeking infertility treatment found many studies in their sample emphasized the need for patient-reported suggestions to improve competency in providers [ 100 ]. The call for patient-reported suggestions highlights the need for increased uptake of community-based participatory research to meaningfully engage historically marginalized populations while empowering them to be an active participant in the creation of research questions and outcomes to improve accessibility and adherence to care [ 101 ]. Current suggestions to improve accessibility include the use of gender-neutral language on forms and signs, the inclusion of all partners for the patients undergoing treatment regardless of their sex, and the breakdown of cis- and heteronormative expectations in healthcare settings [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review examining culturally competent care for the LGBTQ + community seeking infertility treatment found many studies in their sample emphasized the need for patient-reported suggestions to improve competency in providers [ 100 ]. The call for patient-reported suggestions highlights the need for increased uptake of community-based participatory research to meaningfully engage historically marginalized populations while empowering them to be an active participant in the creation of research questions and outcomes to improve accessibility and adherence to care [ 101 ]. Current suggestions to improve accessibility include the use of gender-neutral language on forms and signs, the inclusion of all partners for the patients undergoing treatment regardless of their sex, and the breakdown of cis- and heteronormative expectations in healthcare settings [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to improve the quality and implementation of EBPs for transgender youth should employ communityengaged research methods to ensure that interventions and implementation plans are informed by transgender youth, their caregivers, and other key community members (e.g., gender-affirming care expert providers). 1,64,65 Example of Community-Engaged Research. The application of community-engaged research methods for identifying an EBP needing tailoring for transgender youth was illustrated through a recent qualitative study.…”
Section: Community-engaged Research Methods Since Its Inception Dandi...mentioning
confidence: 99%
“…Third, and relatedly, almost no studies have examined whether the prognostic or prescriptive relation of stress exposure to treatment outcome is moderated by gender, sexual orientation, ethnicity, or their intersection. Research bearing on this important question could be informed by the rich research base examining adaptations of depression treatments and service delivery for individuals with diverse identities (Legha & Miranda, 2020;Sugarman et al, 2021).…”
Section: Summary and Future Directionsmentioning
confidence: 99%